Rg1 alleviates oxidative stress and spermatogonium apoptosis in D-gal-induced testicular toxicity by activating Akt - Ziling Wang; Kunhang Du; Jiying Hou; Hanxianzhi Xiao; Ling Hu; Xiongbin Chen; Lu Wang; Yaping Wang (Taylor & Francis Group, 2023)
ABSTRACTObjectives: High reactive oxygen species (ROS) levels lead to cell death, and the testes are among the most vulnerable organs to oxidative damage. Rg1, an active ingredient extracted from the natural medicine ginseng, has potential anti-inflammatory, antioxidant and antiapoptotic properties. Our previous studies showed that Rg1 can effectively improve spermatogenic function in mice, but the specific mechanism remains unclear. The purpose of this study was to investigate the effect of Rg1 on oxidative stress and spermatogonium apoptosis in D-gal-induced testicular toxicity and elucidate the associated mechanism.Methods: Male C57BL/6 mice at 6-8 weeks of age were intraperitoneally injected with D-gal (200 mg/kg) for 42 days to establish a testicular injury model, and on day 16, 40 mg/kg Rg1-rich saline was injected intraperitoneally. Concurrently, we established an in vitro model of D-gal-damaged spermatogonia, which was treated with Rg1.Results: We found that treatment with the ginsenoside Rg1 reduced D-gal-induced oxidative stress and spermatogonium apoptosis in vivo and in vitro. Mechanistically, we found that Rg1 activated Akt/bad signaling and reduced D-gal-induced spermatogonium apoptosis.Discussion: We provide evidence showing that the antioxidant effect of Rg1 is mediated by the Akt/GSK-3β/NRF2 axis. Based on these findings, we consider Rg1 a potential treatment for testicular oxidative damage.